2000
DOI: 10.1046/j.1365-2249.2000.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines and soluble cytokine receptor induction after IL-12 administration in cancer patients

Abstract: This study shows that subcutaneous administration of increasing doses of IL‐12, once a week, in 21 cancer patients increased the expression of cytokine genes (interferon‐gamma (IFN‐γ), tumour necrosis factor‐alpha (TNF‐α), IP‐10, MIG, IL‐10, IL‐4) in peripheral blood mononuclear cells even at very low doses (30 ng/kg). Surprisingly, no circulating TNF‐α or IL‐4 could be detected in the plasma of patients treated with IL‐12. However, a marked increase of soluble IL‐4 receptor was demonstrated in the plasma of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 58 publications
2
59
0
1
Order By: Relevance
“…In one study, cancer patients receiving increasing doses of IL-12 were profiled for changes in circulating cytokines after treatment [12]. Intriguingly, several potential immunosuppressive mechanisms were engaged upon repeated IL-12 administration, including a Th1 to Th2 shift as illustrated by an increase in IL-10 expression and diminishment of IFN-γ, tumor necrosis factor alpha (TNFα) and IP-10 in the sera of patients repeatedly treated with IL-12 [12,13]. As will be discussed later, this observation indicates a potential limitation for the use of IL-12 as a single agent.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, cancer patients receiving increasing doses of IL-12 were profiled for changes in circulating cytokines after treatment [12]. Intriguingly, several potential immunosuppressive mechanisms were engaged upon repeated IL-12 administration, including a Th1 to Th2 shift as illustrated by an increase in IL-10 expression and diminishment of IFN-γ, tumor necrosis factor alpha (TNFα) and IP-10 in the sera of patients repeatedly treated with IL-12 [12,13]. As will be discussed later, this observation indicates a potential limitation for the use of IL-12 as a single agent.…”
Section: Introductionmentioning
confidence: 99%
“…A paradigmatic scenario occurring in IL-12-mediated tumor rejection involves the cytotoxicity of CD8 ϩ cells, the Th1 differentiation of naive CD4 ϩ cells that can subsequently provide help for tumor-specific priming of CTLs, and an antiangiogenic effect. It has been shown that the IL-12 effect is largely mediated in vivo by IFN-␥ and its correlate molecules CXCL10 and CXCL9 (26,(32)(33)(34). Our experiments confirm the key role of the IFN-␥-CXCL9/CXCL10 axis in the effect of IL-12, but also add new details describing a reciprocal paracrine loop existing between ECs and stimulated PBMC that is regulated by CXCL9 and CXCL10 and does not require the presence of tumor cells as the source of these chemokines (24,49,60,61).…”
Section: Discussionmentioning
confidence: 99%
“…The indirect biologic effects of IL-12 on ECs are mainly exerted by the production of IFN-␥, which in turn stimulates that of CXCL10 and CXCL9 (23,29,(32)(33)(34)(47)(48)(49)(50)(51). In our system, stimulated PBMC either alone or cocultured with ECs produced IFN-␥ transcript as evaluated by RT-PCR.…”
Section: Cxcl9 and Cxcl10 Alter Mmp9 Activity In Ecs And Chemoinvasiomentioning
confidence: 94%
See 1 more Smart Citation
“…IL-12 primarily exerts its anti-tumor effect via indirect interaction with tumor cells by stimulating potent cytokines such as IFN-␥ and TNF-␣. 11 We, therefore, determined the induced production of IFN-␥ and TNF-␣ at 48 h after injection of PAGA/pmIL-12 complexes into CT-26 subcutaneous tumor-bearing BALB/c mice to see whether IL-12 was able to up-regulate these two cytokines. Similar trends were found in both cases (Figures 2 and 3).…”
Section: Gene Expression For Induced Cytokinesmentioning
confidence: 99%